The Histone Variant H2A.W Defines Heterochromatin and Promotes Chromatin Condensation in Arabidopsis - Yelagandula, Ramesh; Stroud, Hume; Holec, Sarah; Zhou, Keda; Feng, Suhua; Zhong, Xuehua; Muthurajan, Uma M.; Nie, Xin; Kawashima, Tomokazu; Groth, Martin; Luger, Karolin; Jacobsen, Steven E.; et al. (Cell, 2014)
Histone variants play crucial roles in gene expression, genome integrity, and chromosome segregation. We report that the four H2A variants in Arabidopsis define different genomic features, contributing to overall genomic organization. The histone variant H2A.W marks heterochromatin specifically and acts in synergy with heterochromatic marks H3K9me2 and DNA methylation to maintain transposon silencing. In vitro, H2A.W enhances chromatin condensation by promoting fiber-to-fiber interactions via its conserved C-terminal motif. In vivo, H2A.W is required for heterochromatin condensation, demonstrating that H2A.W plays critical roles in heterochromatin organization. Similarities in conserved motifs between H2A.W and another H2A variant in metazoans suggest that plants and animals share common mechanisms for heterochromatin condensation. [Display omitted] •Genomic features are marked by combination of H2A variants in Arabidopsis•Heterochromatin is specifically marked by H2A.W in correlation with H3K9me2•H2A.W is required for heterochromatin condensation and silencing•A conserved C-terminal motif of H2A.W promotes chromatin condensation The four H2A variants in Arabidopsis contribute differently to genome organization with H2A.W serving to define and condense heterochromatin.